Soil Load-Bearing Capacity and Development of Root System in Area Under Sugarcane with Traffic Control in Brazil - de Sousa, Allan Charlles Mendes; Farhate, Camila Viana Vieira; de Souza, Zigomar Menezes; Torres, José Luiz Rodrigues; da Silva, Reginaldo Barboza [UNESP] (Springer Nature, 2018)
Attempts to achieve reduced traffic area and favorable conditions for sugarcane field durability have been made increasingly necessary to use traffic control techniques in areas of sugarcane production. Our goal was to assess the benefits of traffic control for sugarcane cultivation areas by using a load-bearing capacity modeling and developing a root system. Our experiment was conducted in a sugarcane cultivation area in the region of Nova Europa, São Paulo, Brazil, by assessing the following treatments: T1 = sugarcane planted with row spacing of 1.50 m managed without autopilot; T2 = sugarcane planted with row spacing of 1.50 m managed with autopilot; T3 = sugarcane planted with row spacing of 1.5 × 0.90 m managed with autopilot. Soil sampling occurred at layers of 0.00–0.15 and 0.15–0.30 m in inter-row center and seedbed region. Our results reveal that the use of autopilot in the seedbed area is less influenced by machinery traffic, which guarantees preserved soil structure maintenance in the plant row region. Mathematical models of the inter-row center presented higher load-bearing capacity values than the seedbed region for all treatments, layers, and cycles assessed. Additionally, load-bearing capacity increases as the sugarcane cultivation cycles evolve, including higher soil load-bearing capacity at the first ratoon cane cycle in relation to the cane-plant cycle. Finally, the sugarcane crop root system has good distribution during the cane-plant cycle; however, the first ratoon cane cycle has a downward trend for the plant rows in the inter-row center because of intensive machine traffic.
Keywords: Entisols Quartzipsamments; Modeling; Root growth; Soil compaction; Soil physics; Soil structure